Hourly-resolution analysis of electricity decarbonization in Spain (2017–2030). (1st January 2019) - Victoria, Marta; Gallego-Castillo, Cristobal
Highlights: Hourly-resolved model to investigate highly-renewable electricity generation in Spain. Correlation analysis of time series to create 900 combinations used in simulations. Transition paths evaluated based on security of supply, CO2 emissions, and renewable share. Short-term phase-out of nuclear and coal power plants proven to be feasible. Abstract: Two alternative paths to achieve highly-renewable electricity generation in peninsular Spain are investigated in this paper. Every transition path comprises a description of the installed and decommissioned generation and storage capacities, from 2017 to 2030, as well as a hypothesis on the evolution of the electricity demand. The electricity mix for every hour within the transition path is determined through a dispatch algorithm that prioritizes electricity from renewable energy sources. The simulation is run for 900 different combinations of time series representing the hourly capacity factors of different technologies, as well as the electricity demand. This robust approach allows the evaluation of the transition paths based on the statistical distribution of several defined assessment criteria, such as security of supply, CO2 emissions or renewable share in electricity generation. The feasibility of a Spanish power system with high renewable penetration is investigated not only in a future reference year but throughout the transition path. In particular, a progressive and simultaneous phase-out of nuclear and coal power plants in the short-term is proven to be feasible. Furthermore, the results sensitivity is analyzed including scenarios with a delayed nuclear phase-out, lower hydroelectricity generation due to more frequent and severe droughts caused by climate change and higher annual increment for the electricity demand.